PERAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DALAM MENINGKATKAN PENGARUH PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Viyanandrie Asmoro Kusuma Dirga; Sutianingsih Sutianingsih (JURNAL ILMIAH EDUNOMIKA, 2024)
This study examines how organisational citizenship behavior (OCB) mediates the influence of training, and organisational culture, on employee performance. The number of respondents was 30 employees of SAMSAT Boyolali testing using linear regression. Data is collected through surveys. Training and organizational culture affect OCB significantly. Employee performance is heavily influenced by training, organizational culture, and OCB. Through OCB, training variables and organizational culture have a real effect on employee performance. Keywords : organisational citizenship behavior (OCB) training, organisational culture, employee performance